Supporting Jobs in Fragility, Conflict, and Violence Situations - Von Der Goltz, Jan; Mavridis, Dimitris (World Bank, Washington, DC, 2020)
This Jobs Solutions Note identifies practical solutions for development practitioners and policymakers to design and implement policies and programs that improve jobs outcomes for in FCV contexts. Based on curated knowledge and evidence for a specific topic and relevant to jobs, the Jobs Solutions Notes are not intended to be exhaustive; they provide key lessons, solutions and approaches synthesized from the experiences of the World Bank Group and partners. This Note draws in part on the Integrated Framework for Jobs in Fragile and Conflict Situations and Generating employment in poor and fragile states: Evidence from labor market and entrepreneurship programs.